1993
DOI: 10.1007/bf00211433
|View full text |Cite
|
Sign up to set email alerts
|

Moderate maternal drinking and outcome of pregnancy

Abstract: The adverse effect of light or moderate maternal drinking during pregnancy on the well being of the newborn has been investigated. The study group included 2145 live births in the obstetric units of 11 Italian cities between February 1989 and July 1990. A detailed life style questionnaire was administered to the mothers. Information on the newborn was collected from clinical records as well as from a clinical examination. Both univariate and multivariate analyses were suggestive of a decrease in mean birth wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 15 publications
2
33
2
Order By: Relevance
“…Only maternal drinking of 20 g of absolute alcohol per day increased the risk for preterm birth as Lazzaroni and colleagues reported. 10 Similar are the findings of Parazzini et al, 11 who showed an increased risk of preterm birth for mothers drinking three or more units of alcohol per week in pregnancy. Within this study sample, we could not find a correlation between alcohol consumption and preterm birth probably because of the low exposure, confirming the findings of Jaddoe et al 12 We believe the association between ethanol handling and preterm birth (which was not significant) is a coincidence because of the relatively small numbers (n ¼ 11), especially because solvents such as ethanol are generally handled under a hood.…”
Section: Discussionsupporting
confidence: 70%
“…Only maternal drinking of 20 g of absolute alcohol per day increased the risk for preterm birth as Lazzaroni and colleagues reported. 10 Similar are the findings of Parazzini et al, 11 who showed an increased risk of preterm birth for mothers drinking three or more units of alcohol per week in pregnancy. Within this study sample, we could not find a correlation between alcohol consumption and preterm birth probably because of the low exposure, confirming the findings of Jaddoe et al 12 We believe the association between ethanol handling and preterm birth (which was not significant) is a coincidence because of the relatively small numbers (n ¼ 11), especially because solvents such as ethanol are generally handled under a hood.…”
Section: Discussionsupporting
confidence: 70%
“…There were no consistent effects on miscarriage (Armstrong et al, 1992;Kesmodel et al, 1987;Windham et al, 1998), stillbirth (Faden et al, 1997), IUGR (Lundsberg et al, 1997;McDonald et al, 1992;Whitehead and Lipscomb, 2003), low birthweight (Lazzaroni et al, 1993;Marbury et al, 1983;O'Callaghan et al, 2003;Ogston and Parry, 1992), preterm birth (Albertsen et al, 2004;Lazzaroni et al, 1993;McDonald et al, 1992), and malformations (Marbury et al, 1983;Mills and Graubard, 1987;Polygenis et al, 1998). For instance, a few studies found an increase in risk for low birthweight (Lundsberg et al, 1997;Virji, 1991) or IUGR (Windham et al, 1995) among children of mothers with moderate consumption, whereas others even have reported a possible protective effect .…”
mentioning
confidence: 82%
“…According to Abel (1996), the increases in birth weight in epidemiological studies related to moderate drinking during pregnancy (Mills et al, 1984;Lumley et al, 1985;Kline et al, 1987;Little and Wendt, 1991;Godel et al, 1992;Larroque et al, 1993;Lazzaroni et al, 1993;Primatesta et al, 1993) have received little attention. In contrast to the human studies where the increase in body weight, even though slight-tomodest, is not uncommon, it has been rarely reported in animal studies.…”
Section: Effects On Birth Weightmentioning
confidence: 97%